Novel 2-indolinone benzylpiperidine- thiosemicarbazone hybrids as cholinesterase inhibitors: Design, synthesis and biological evaluation - Sevincli, Zekiye Seyma; Soylu-Eter, Ozge; Hasbal-Celikok, Gozde; Altiparmak-Ulbegi, Gulsum; Bayir, Ece; Sendemir, Aylin; Karali, Nilgun (Academic Press Inc Elsevier Science, 2026)
The design of this study was based on donepezil, a selective acetylcholinesterase (AChE) inhibitor used in the treatment of AD, consisting of an 1-indanone ring and a benzylpiperidine moiety. For this purpose, the 1-indanone ring was replaced with a 2-indolinone ring and new hybrid compounds were designed by connecting the benzylpiperidine residue to the 2-indolinone ring via the thiosemicarbazone bridge. Based on the results of in silico studies, 29 new 2-indolinone benzylpiperidine-thiosemicarbazone hybrid compounds (10a-n and 11a-o) were selected and synthesized. The in vitro anti-cholinesterase (ChE) activities of the compounds were determined and compared with donepezil (IC50 = 0.44 & micro;M for AChE and IC50 = 4.70 & micro;M for BuChE). Compound 11e showed the strongest inhibition (IC50 = 0.91 & micro;M for AChE and IC50 = 30.97 & micro;M for BuChE), while compounds 11a, 11b, 11d, 11g, 11k, 11l and 11n also displayed strong AChE inhibitory activity (range of IC50 = 1.15-3.13 & micro;M). Compounds showed weak or no inhibition against BuChE. The cytotoxic effects of the active compounds were evaluated in HUVEC cell lines, and non-cytotoxic effects were observed for compounds 11b, 11d, 11e and 11k. Neuroprotective effect studies of active and non-cytotoxic compounds in HUVEC cells were performed in SH-SY5Y cells exposed to H2O2-induced damage. According to the results, compounds 11e and 11k exhibited significant neuroprotective effects in damaged SH-SY5Y cells, with the compound 11e showing higher protective effect than compound 11k. Compound 11e exhibited a markedly higher permeability across the blood-brain barrier (BBB) model. Compound 11e was selected as the lead candidate based on mechanistic findings. Molecular dynamics simulation of compound 11e was performed on the AChE binding pocket.
Keywords: 2-Indolinone; Thiosemicarbazone; Benzylpiperidine; Anti-Cholinesterase; Neuroprotection; Blood-Brain Barrier